Exploring the Role of Elementary School Teachers as Counselors: Perceptions, Practices, and Challenges in Student Support - Ahmad Rifqy Asshidiqy; Rohmah Ageng Mursita; Puji Yuniarti; Siti Ayu Jahrotun Nisa Annur; Rossa Nurmalinda (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The purpose of this study is to delve into the changing role of elementary school teachers as counselors, examining attitudes, practices, and barriers to providing emotional and mental health support. This study, conducted at Medalsari Elementary School in the Karawang Regency, West Java, also emphasizes the need for teachers’ involvement in cultivating and sustaining students’ social-emotional health, particularly in rural areas where mental health professionals are scarce. The qualitative methodology of the study employs surveys and open-ended questions, which enable the exploration of teachers' understanding of counselling, the practices they utilise, and the barriers they face. Teachers know they have two jobs and one is critical, being a counselor as well as an educator, but it’s hard to do both because there isn’t enough time, training, or resources. Despite these challenges, teachers implement techniques  such as speaking directly to students, practicing mindfulness, and approaching parents. The study highlights the need for enhanced professional development and organisational support to adequately integrate counselling into teachers' roles. Keywords: elementary school teachers, counseling, social-emotional support, rural education, teacher training